The Effect of Shadow Training on Backhand Drive Accuracy in Table Tennis Players - Akmal Komara Trisna Jaya Santika Jatnika; Indra Safari; Adang Sudrazat (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
This study aimed to examine the effect of shadow training on the accuracy of backhand drive strokes among table tennis players at PTM Truna. Backhand drive is an essential technique in table tennis that requires speed, coordination, and stroke accuracy. However, many club-level athletes still experience difficulties in maintaining consistent and accurate strokes due to improper technique and limited technical training. This study employed a pre-experimental method using a one-group pretest-posttest design. The sample consisted of 20 table tennis players selected using a total sampling technique. The instrument used was a backhand drive accuracy test. Data were analyzed using normality tests followed by a paired sample t-test. The results showed that the mean score increased from 47.15 in the pretest to 58.65 in the posttest. The paired sample t-test demonstrated a significant difference between pretest and posttest scores (p < 0.05), indicating that shadow training significantly improved backhand drive accuracy. In addition, the effect size analysis showed that the training produced a strong practical effect on athletes’ performance. These findings indicate that shadow training is effective in improving technical stroke accuracy in table tennis players. This study provides empirical evidence regarding the effectiveness of shadow training at the local club athlete level and contributes to the development of technical training methods in table tennis.